Pelaksanaan Ekstrakurikuler Seni Tari (Randai) di MTsN 3 Kota Padang - Wa’afini Wa’afini; Susmiarti Susmiarti (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The implementation of extracurricular dance at MTsN 3 Padang City is specifically research conducted to find out how students' interest in implementing extracurricular dance includes indicators of feelings of pleasure, interest, attention and involvement. This type of research is qualitative research with descriptive methods. The data collection techniques used were observation, interviews, questionnaires and documentation to find out directly about the implementation of arts extracurriculars at MTsN 3 Padang City. Then the results of the observations and interviews carried out in this research are described and described. The material taught is about randai. The teaching method used is discussion followed by practice. Based on the results of data analysis, 12 students who took part in the extracurricular, consisting of classes VII and VIII, showed that the interest of the students who took part in the Randai extracurricular can be categorized as good with an average score of 69%, because this method makes students feel interested and engaged. Regarding the extracurricular activities taught, students also often practice together and discuss movements and scripts that they do not yet understand. So the Randai extracurricular activities at MTsN 3 Padang City are running very well.